2020
DOI: 10.3390/ijms21228821
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages vB_Sen-TO17 and vB_Sen-E22, Newly Isolated Viruses from Chicken Feces, Specific for Several Salmonella enterica Strains

Abstract: Two newly discovered bacteriophages, isolated from chicken feces and infecting Salmonella enterica strains, are described in this report. These phages have been named vB_Sen-TO17 and vB_Sen-E22, and we present their molecular and functional characterization. Both studied viruses are able to infect several S. enterica strains and develop lytically, but their specific host ranges differ significantly. Electron microscopic analyses of virions have been performed, and full genome sequences were determined and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Therefore, the aim of this work was to compare the efficacy and various biological parameters between phage therapy and the use of antibiotics in chickens infected with S. enterica serovar Typhimurium which is one of the most common serovars responsible for poultry infections. The concept of this study was to use two recently discovered and described by us bacteriophages, vB_SenM-2 ( Kosznik-Kwaśnicka et al., 2020a ) and vB_Sen-TO17 ( Kosznik-Kwaśnicka et al., 2020b ), and two antibiotics, colistin and enrofloxacin, frequently used in veterinary practice to treat poultry although the latter antibiotic is quite controversial due to its adverse effects, but on the other hand it is one of the most effective antibacterial drugs used in veterinary medicine (it is not approved to be used in humans) ( Sohail et al., 2021 ; Grabowski et al., 2022 ). The two phages were used together as a cocktail, as this combination of SenM-2 and vB_Sen-TO17 has been found recently to be effective against S. enterica strains and safe for eukaryotic cells in in vitro studies and in experiments with the Galleria mellonella animal model ( Kosznik-Kwaśnicka et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of this work was to compare the efficacy and various biological parameters between phage therapy and the use of antibiotics in chickens infected with S. enterica serovar Typhimurium which is one of the most common serovars responsible for poultry infections. The concept of this study was to use two recently discovered and described by us bacteriophages, vB_SenM-2 ( Kosznik-Kwaśnicka et al., 2020a ) and vB_Sen-TO17 ( Kosznik-Kwaśnicka et al., 2020b ), and two antibiotics, colistin and enrofloxacin, frequently used in veterinary practice to treat poultry although the latter antibiotic is quite controversial due to its adverse effects, but on the other hand it is one of the most effective antibacterial drugs used in veterinary medicine (it is not approved to be used in humans) ( Sohail et al., 2021 ; Grabowski et al., 2022 ). The two phages were used together as a cocktail, as this combination of SenM-2 and vB_Sen-TO17 has been found recently to be effective against S. enterica strains and safe for eukaryotic cells in in vitro studies and in experiments with the Galleria mellonella animal model ( Kosznik-Kwaśnicka et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been growing interest in the use of lytic bacteriophages as an innovative bio-preservative of fresh and minimally processed food products that can inhibit the growth of food-borne pathogens and spoilage microorganisms [22,24,25]. The use of bacteriophages in the biocontrol of a variety of bacterial pathogens has been studied in raw chicken meat [26][27][28], fresh-cut fruits [29,30], and fresh products including sprout seeds [22,31,32] and lettuce [33,34]. The important feature of bacteriophages is that they do not pose a health risk to consumers because they are strain-specific bacterial viruses and do not cause damage to the gut microbiome of the host [24,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to ensure global food safety and preserve the quality of these food products [5]. To ensure food safety and the long shelf-life of foods, it is important to understand food spoilage mechanisms and food preservation techniques [28]. However, increasing the shelf-life of foodstuff without compromising the original food properties is still critical and challenging [40,[47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…The MOI of PSDA-2 is 0.001, and the latent period is 10 min, which is shorter than Salmonella phage vB_SenS_SE1 (40 min), vB_SPuM_SP116 (20min) [ 49 ], SS3e (20 min) [ 50 ], and is equivalent to vB_SenTO17 (10–20 min) [ 51 ]. The exponential phase of PSDA-2 is 50 min, and the burst size is 120 pfu/cell, which is higher than vB_SenS_SE1 (19 pfu/cell), SS3e (98 pfu/cell), vB_SenTO17 (10–80 pfu/cell), and is equivalent to vB_SPuM_SP116 (118pfu/ cell).…”
Section: Discussionmentioning
confidence: 99%
“…The titer of PSDA-2 is almost unchanged between pH 3–10, which makes it suitable for a wide range of applications. PSDA-2 can only lyse S .Typhimurium within the range of tested strains, which is similar to the evolutionary related phages vB_SenS_SE1 and vB_SenTO17 [ 51 ]. But limited by the small number of bacterial strains used for host range, it can only be concluded that PSDA-2 has the relatively strict host specificity.…”
Section: Discussionmentioning
confidence: 99%